A population‐based, cross‐sectional study of the prevalence and correlates of sedentary behaviour of adults with intellectual disabilities. Issue 1 (7th December 2017) - Melville, C. A.; McGarty, A.; Harris, L.; Hughes‐McCormack, L.; Baltzer, M.; McArthur, L. A.; Morrison, J.; Allan, L.; Cooper, S.‐A.
Abstract: Background: High levels of sedentary behaviour have a negative impact on health and well‐being. There is limited evidence on the prevalence and correlates of sedentary behaviour of adults with intellectual disabilities (ID). Methods: A population‐based sample of adults with ID were invited to take part in a comprehensive health check programme. Demographic and health data were collected during a structured interview and physical examination. Screen time was used as a proxy measure of sedentary behaviour. Bivariate and multivariate statistical modelling examined correlates of screen time. Results: Fifty per cent of the 725 participants reported four or more hours of screen time per day. Male gender, higher levels of intellectual ability, mobility problems, obesity, not having hearing impairment and not having epilepsy were all significantly associated with higher screen time in the final multivariate model (R 2  = 0.16; Hosmer–Lemeshow goodness of fit statistic P  = 0.36). Conclusions: This is the first study to publish population‐based data on the prevalence and correlates of sedentary behaviour in adults with ID. Compared with adults who do not have ID, adults with ID have higher levels, and different correlates, of sedentary behaviour. A better understanding of the social context of sedentary behaviour will inform the design of effective behaviour change programmes for adults with ID.